Qur’anic Parenting: An Analytical Study of Ibn Kathir’s Exegesis on Surah Luqman (Verses 12–19): Parenting Qurani: Studi Analisis Tafsir Ibnu Katsir pada Q.S Luqman (Ayat 12-19) - Syahrani, Aprilia; Laili Liddini (Averroes: Journal for Science and Religious Studies, 2025)
Main Focus: The main focus of this study is to explore the concept of parenting from the Qur’anic perspective based on Ibn Kathir’s interpretation of Surah Luqman, verses 12–19. It aims to uncover the parenting values taught by Luqman to his son. Research Questions: This research addresses the forms of Luqman’s advice as interpreted by Ibn Kathir and the parenting values contained therein. Methodology: This study employs a library research approach, analyzing books and other relevant literature using content analysis methodology. Findings: The study reveals that Luqman’s advice embodies key parenting principles, including the instillation of monotheism (tawhid), awareness of God’s supervision, the importance of worship, enjoining good and forbidding evil, patience, and the development of humility and social ethics. These principles are highly applicable to contemporary parenting practices. Significance: This research contributes to the enrichment of Islamic parenting literature by offering a revelation-based parenting model that can be contextually applied in today’s Muslim family life. Conclusion: The study concludes that Luqman’s parenting serves as a relevant and transformative model of character education.